Steps towards sustainable manufacturing through modelling material, energy and waste flows - Smith, Leigh; Ball, Peter D. (Elsevier Science B.V., Amsterdam., 2012)
A sustainable society cannot be realised without more efficient approaches and technologies, which must in part be provided by manufacturing. Available literature covers the principles for making manufacturing more sustainable, but there is little, if any, practical guidance to show how to apply these principles. Lower level guidelines are required to provide guidance on systematically analysing manufacturing facilities and to assist with the identification and selection of improvement opportu- nities. This paper reports on work to develop guidelines for Material, Energy and Waste (MEW) process flow modelling to support the pursuit of sustainable manufacturing. Using qualitative MEW process flow maps of a case facility, data was collected to build a spreadsheet model aligned to each of the MEW process flows. The quantitative analysis provided detailed insight into the MEW process flows within the system and assisted with the identification and selection of environmental efficiency improve- ments. The key learning points from conducting the analysis generated a set of guidelines to aid the analysis of manufacturing systems, using MEW process flow modelling. This paper documents the approach developed and the environmental performance improvement opportunities identified in the case facility.
Keywords: Process mapping; Sustainable manufacture; Zero carbon; Material energy and waste modelling